2015
DOI: 10.1002/aur.1580
|View full text |Cite
|
Sign up to set email alerts
|

Looking, seeing and believing in autism: Eye movements reveal how subtle cognitive processing differences impact in the social domain

Abstract: LOOKING, SEEING AND BELIEVING IN AUTISM 2 Lay AbstractAdults with High Functioning Autism (ASD) viewed scenes with people in them, whilst having their eye movements recorded. The task was to indicate, using a button press, whether the pictures were normal, or in some way weird or odd. Oddities in the pictures were categorized as violations of either perceptual or social norms. Compared to a Typically Developed (TD) control group, the ASD participants were equally able to categorise the scenes as odd or normal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…Since imitation has been reported to be reduced in autism for direct eye gaze conditions, but not for averted eye gaze conditions [60], it could be inferred that the use of direct gaze may hinder imitation in ASD. The relationship of atypical visual processing for salient social cues (direct eye gaze or head turning) and poorer imitation performance in autism, as revealed in these two studies [59,60], support the hypothesis that subtle differences in social processing have the potential to impact in social interaction behaviours in everyday communication in autism, and that hypothesis is also supported by many other studies [61,62,63].…”
Section: Joint Attention Paradigmssupporting
confidence: 78%
See 4 more Smart Citations
“…Since imitation has been reported to be reduced in autism for direct eye gaze conditions, but not for averted eye gaze conditions [60], it could be inferred that the use of direct gaze may hinder imitation in ASD. The relationship of atypical visual processing for salient social cues (direct eye gaze or head turning) and poorer imitation performance in autism, as revealed in these two studies [59,60], support the hypothesis that subtle differences in social processing have the potential to impact in social interaction behaviours in everyday communication in autism, and that hypothesis is also supported by many other studies [61,62,63].…”
Section: Joint Attention Paradigmssupporting
confidence: 78%
“…The results from the eye-movement studies reported so far are not entirely consistent and the eye-movement measures reported suggest that there are both similarities and differences in social processing in autism. There are, however, very subtle differences in visual processing of social stimuli in different social contexts [61,113,114]. For example, Benson et al [61] revealed that, compared to TD adults, when deciding whether a social scene is weird or normal, high-functioning adults with autism fail to recognize the socially weird information during their initial fixation on that information (see Figure 4 and Figure 5).…”
Section: Stimulus and Task Complexitymentioning
confidence: 99%
See 3 more Smart Citations